لغة حمير وعلاقتها باللغة العربية الفصحى : دراسة وصفية وتحليلية - قحطاني، زينة حسين عوضه (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
This research addresses the dialects of Himyar and their relations with formal Arabic as they have not been sufficiently studied in modern studies. This language has not received the attention of previous and present researchers since there are no broad and serious studies about the language of Himyar. Despite its fame among the Arab southern tribes, the research, in an effort to explain the role southern dialects play in formal Arabic, attempts to highlight these linguistic phenomena because the language of Himyar is one of the southern 'Aribah languages. The research also demonstrates the tribe of Himyar throughout history and their power and presents the southern Musnad calligraphy that ancient Himyar epigraphy was written in which later became an important history that reserves the Arabic and root nature of the Himyar language. The research traces the Musnad calligraphy and the symbols used to refer to some vocabularies by the Himyar people; which the Himyarian knew and wrote upon skins, plates and stones and left remaining effects for this calligraphy. Some of these tribes which reserve this language are Bani Malik and Faifa in southern Saudi Arabia. It also emphasizes the exchange of daily conversations in the Himyar language and writing in Arabic alphabet. This study compiles various vocabularies, examples, poetries, tales, proverbs and others among those tribes which are known for using this language. Moreover, the study traces the language of Himyar, its four levels and all of its aspects morphologically, acoustically, grammatically, and that found in dictionaries. The study also adopted two approaches. First, the descriptive approach as it studies the language of Himyar and its evolution. Second, the analytical approach, as the study determines the sounds of the language of Himyar and its writing symbols and numbers, then the morphological structure and grammatical rules in the language and the semantics of vocabularies based on dictionary and context and compares it with formal Arabic. This will benefit researchers of anthropological studies to further conduct a linguistic and population survey of the Himyar language and its geographical distribution. It will also be useful in the field of social language and the geographical science language.